2019
DOI: 10.1055/s-0038-1676660
|View full text |Cite
|
Sign up to set email alerts
|

Intervening in the Acute Phase of Postradiation Carotid Blowout Syndrome

Abstract: Introduction Acute carotid blowout syndrome (aCBS) is a severe complication of head and neck cancer (HNC). It can be defined as a rupture of the extracranial carotid arteries, or one of their branches, that causes life-threatening hemorrhage, and which nowadays can be treated with urgent endovascular intervention. Objective We retrospectively evaluate the endovascular management of aCBS and its outcome in years of survival. Methods Retrospectively, we describe our experience with endova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…However, in the case of internal carotid artery hemorrhage, vascular interventional embolization or a covered stent may be used, depending on the pattern of intracranial artery vascularization. Jung et al found that the average survival time in such patients could be increased by 9 months through the use of interventional therapy [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of internal carotid artery hemorrhage, vascular interventional embolization or a covered stent may be used, depending on the pattern of intracranial artery vascularization. Jung et al found that the average survival time in such patients could be increased by 9 months through the use of interventional therapy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Carotid blowout syndrome (CBS) is one of the serious life-threatening complications seen in 3%-4% of head and neck cancers [1] . It usually occurs by forming erosion in the head and neck vessels of patients with advanced cancer who have received radiotherapy [2] . Mortality rates have been reported to be over 50% [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It usually occurs by forming erosion in the head and neck vessels of patients with advanced cancer who have received radiotherapy [2] . Mortality rates have been reported to be over 50% [ 2 , 3 ]. There are different treatment approaches such as open surgical ligation, endovascular treatment techniques, and extracranial/intracranial vascular bypass [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Recently, endovascular intervention by means of balloon occlusion, coil embolization or covered stent-graft placement has been advocated as first line of treatment for CBS. 6,7…”
Section: Introductionmentioning
confidence: 99%